2013
DOI: 10.1371/journal.pone.0082845
|View full text |Cite
|
Sign up to set email alerts
|

Brain Network Evolution after Stroke Based on Computational Experiments

Abstract: Stroke is a frequently-occurring disease threatening the human nervous system. As a serious debilitation affecting a large-scale, hierarchical, and vastly complex electrochemical system, stroke remains relatively misunderstood. Rehabilitation mechanisms and means have suffered from this lack of systematic understanding. Here we propose an evolution model to simulate the dynamic actual evolvement process of functional brain networks computationally in an effort to address current shortcomings in the state of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…Small-worldness reflects an optimal network structure associated with rapid synchronization and information transfer, minimal wiring costs, as well as a balance between local processing and global integration ( Watts and Strogatz, 1998 ). However, it is still not clear whether clinical recovery after stroke is paralleled by a decreased small-world organization of the brain (or parts of it), as suggested by some studies ( Wang et al, 2010 ; Caliandro et al, 2017 ) or, on the contrary, by an increased small-worldness, as suggested by others ( Tsirka et al, 2011 ; De Vico Fallani et al, 2012 ; Li et al, 2013 ). Several factors may in fact influence the evolution of the small-world parameter, such as patient cohort, phase of stroke, lesion type, brain areas investigated, brain signals (e.g., fMRI or EEG), band selected, etc.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Small-worldness reflects an optimal network structure associated with rapid synchronization and information transfer, minimal wiring costs, as well as a balance between local processing and global integration ( Watts and Strogatz, 1998 ). However, it is still not clear whether clinical recovery after stroke is paralleled by a decreased small-world organization of the brain (or parts of it), as suggested by some studies ( Wang et al, 2010 ; Caliandro et al, 2017 ) or, on the contrary, by an increased small-worldness, as suggested by others ( Tsirka et al, 2011 ; De Vico Fallani et al, 2012 ; Li et al, 2013 ). Several factors may in fact influence the evolution of the small-world parameter, such as patient cohort, phase of stroke, lesion type, brain areas investigated, brain signals (e.g., fMRI or EEG), band selected, etc.…”
Section: Discussionmentioning
confidence: 97%
“…Previous works have shown that brain networks of patients in both acute and subacute phases of stroke present rearrangements with respect to controls, which could be detected by measuring the network small-worldness ( Wang et al, 2010 ; Tsirka et al, 2011 ; De Vico Fallani et al, 2012 ; Li et al, 2013 ; Caliandro et al, 2017 ). Small-worldness reflects an optimal network structure associated with rapid synchronization and information transfer, minimal wiring costs, as well as a balance between local processing and global integration ( Watts and Strogatz, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…For each individual, the brain images ( Fig. 1a ) were parcelled into 90 ROIs by automatic anatomical labelling (AAL) 26 27 28 , as shown in Fig. 1b (the names of the ROIs are provided in the Supplementary materials ).…”
Section: Methodsmentioning
confidence: 99%
“…So far, only very few models have addressed dynamic changes in network topology after brain lesions. Li et al ( 2013 ) described changes in topology merely phenomenologically and did not include any neuronal mechanism such as the formation and deletion of synapses. Others have applied neural mass models with various rules of plasticity and assessed by graph theoretical methods the changes in inter-area connectivity in response to lesions and degeneration (Rubinov et al, 2009 ; Stam et al, 2010 ; de Haan et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%